THE ROLE OF NATURE-BASED LEARNING MODEL IN INCREASING STUDENT LEARNING MOTIVATION AT SD ISLAM ALAM JUNUDURAHMAN CIJEDIL CIANJUR - Sulis Tyaningsih; Kun Nurachadijat (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Education functions as assistance given to children in their physical and mental growth to reach maturity and takes place in an educational institution. Along with the changing times, schools have emerged that have their own characteristics in achieving excellent school programs. The results showed that the purpose of education at Sekolah Alam Junudurahman is to achieve students who have faith and devotion, and there are special programs such as Outbound, farming, entrepreneurship, literacy, art performances, and student work. SD Alam Islam Junudurahman is an alternative school created to meet the expectations of parents who want to send their children to an Islamic-based school and a good environment, with a learning concept that is realized in the right vision and mission, a representative school profile as a superior school, an academic curriculum combined with a non-academic curriculum in shaping the characteristics of students, as well as learning methods and models that make children more familiar with nature and the environment. The learning evaluation shows that the activities are in accordance with the standards in achieving the target in completing the learning.